2-((1H-Benzo[d]imidazol-2-yl)amino)benzo[d]thiazole-6-sulphonamides: a class of carbonic anhydrase II and VII-selective inhibitors - Morteza Abdoli; Claudiu T. Supuran; Raivis Žalubovskis (Journal of Enzyme Inhibition and Medicinal Chemistry, 2023)
A small library of substituted cyclic guanidine incorporated benzothiazole-6-sulphonamides was synthesized. All obtained compounds were investigated for their inhibitory activity against the key brain-associated human carbonic anhydrase isoform hCA VII (a promising target for the treatment of neuropathic pain) and three isoforms expressed in brain and other tissues, hCA I, II, and IV. Sulphaguanidine derivatives 9a–d were inactive on the all investigated isoforms while the primary sulphonamide containing guanidines 6a–c and 7a–c were inactive towards hCA IV but displayed inhibiting properties on hCA I, II, and VII with KIs values in the low nanomolar to micromolar ranges. The results indicated that isoforms hCA II and VII were potently and selectively inhibited by these compounds, whereas the cytosolic hCA I was less sensitive to inhibition. The derivatives reported in this study might be useful for design of more potent and selective inhibitors of hCA II and VII.